Safety of allergen‐specific immunotherapy in children. (25th January 2022) - De Filippo, Maria; Votto, Martina; Caminiti, Lucia; Panasiti, Ilenia; Carella, Francesco; De Castro, Giovanna; Landi, Massimo; Olcese, Roberta; Vernich, Mario; Marseglia, Gian Luigi; Ciprandi, Giorgio; Barberi, Salvatore
Abstract: Allergic respiratory diseases, such as asthma and allergic rhinitis, are global health issues and have had an increasing prevalence in the last decades. Allergen‐specific immunotherapy (AIT) is the only curative treatment for allergic rhinitis and asthma, as it has a disease‐modifying effect. AIT is generally administered by two routes: subcutaneous (SCIT) and sublingual immunotherapy (SLIT). Local side effects are common, but usually well‐tolerated and self‐limited. However, systemic side effects are rare, and associated with uncontrolled asthma and bronchial obstruction, or related to errors in administration. Physicians should constantly assess potential risk factors for not only reporting systemic reactions and fatalities but also implementing other therapies to improve AIT safety. This paper highlights recent evidence on local and systemic reactions related to SCIT and SLIT in children.